Analisis Determinan Pendapatan Driver Grab di Kota Denpasar - Juwandi Juwandi; Ni Luh Karmini (Lembaga Pengembangan Kinerja Dosen, 2026)
Grab is a technology-based company that provides online transportation services through a pick-up and drop-off system, serving as a solution to the limitations of conventional motorcycle taxis that are bound by station locations and working hours. Based on a survey conducted by the Institute for Development of Economic and Finance (INDEF), 82.6% of Indonesians use Grab as their preferred online transportation service, compared to Gojek, which is only 57.3%. This study aims to determine the effect of on-bid activity, work experience, capital, and feature activation on the income of Grab two-wheeler drivers in Denpasar City, both simultaneously and partially. The research method used is multiple linear regression analysis with the assistance of the SPSS application. The results show that simultaneously, the variables on-bid activity, work experience, capital, and feature activation have a significant effect on the income of Grab two-wheeler drivers in Denpasar City. Partially, each of these variables also has a positive and significant effect on driver income. This means that higher on-bid activity, longer work experience, greater capital, and optimal use of application features contribute to higher income for Grab drivers. Users of Grab services are expected to provide objective appreciation to drivers by giving ratings according to the quality of service received.